2018
DOI: 10.1557/adv.2018.489
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin biotemplated platinum aerogels

Abstract: Here gelatin biotemplated platinum aerogels were prepared from gelatin hydrogels equilibrated in K2PtCl4solutions ranging from 1-250 mM and reduced with sodium borohydride before supercritical drying in liquid CO2. Scanning electron microscopy revealed an average ligament diameter of 40.6 ± 9.7 nm and a pore size range of ∼10 – 200 nm. Thermogravimetric analysis correlated the ratio of metal content to biotemplate mass as a function of equilibrated platinum ion solution, and X-ray diffractometry indicated plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The structure of the nanofibrils and growth of the noble metal nanoparticles indicates the effects of reduction on the silk fibroin. It has been previously demonstrated that the reduction of these noble metals can be completed using gelatin and cellulose materials with higher reducing agent concentrations [4,5]. Figure 2 shows the SEM images of the silk fibroin aerogel with platinum and palladium after reduction with 100 mM sodium borohydride.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structure of the nanofibrils and growth of the noble metal nanoparticles indicates the effects of reduction on the silk fibroin. It has been previously demonstrated that the reduction of these noble metals can be completed using gelatin and cellulose materials with higher reducing agent concentrations [4,5]. Figure 2 shows the SEM images of the silk fibroin aerogel with platinum and palladium after reduction with 100 mM sodium borohydride.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lower pH, gold metal ions are more attracted to the silk molecular structure caused by electrostatic interactions, which is visible as a higher density of decorated surface nanoparticles compared with the silk–platinum and silk–palladium aerogels (Figure S3). This has been discussed in other biopolymer-related work [4,5]. Silk fibroin has a repeating pattern of glycine, serine, and alanine forming polymer blocks with shorter block regions of non-repeating sequences [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group’s recent reports on direct reduction synthesis of noble metal aerogels [ 39 ] and salt-templated platinum macrobeams [ 40 ] suggest a possible route to achieving bi- and tri-metallic three-dimensional Au-Cu and Au-Cu-Pd nanostructures. The use of these synthesis methods in conjunction with biotemplating has also demonstrated the versatility of these approaches to yield porous noble metal structures [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%